2010
DOI: 10.1002/elps.200900738
|View full text |Cite
|
Sign up to set email alerts
|

Separation of propranolol enantiomers by CE using sulfated β‐CD derivatives in aqueous and non‐aqueous electrolytes: Comparative CE and NMR study

Abstract: Separations using CE employing non-aqueous BGE are already as well established as separations in aqueous buffers. The separation mechanisms in achiral CE with non-aqueous BGEs are most likely similar to those in aqueous buffers. However, for the separation of enantiomers involving their interaction with chiral buffer additives, the interaction mechanisms might be very different in aqueous and non-aqueous BGEs. While the hypothesis regarding distinct mechanisms of enantiomer separations in aqueous and non-aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
61
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 24 publications
9
61
0
Order By: Relevance
“…The significant signal splittings were observed not only for the aromatic but also for some alkyl chain protons of propranolol (data not shown). Thus, in confirmation to our previous results [10,14], not only can enantioseparation in CE but also signal splitting in 1 H NMR spectra be observed without inclusion (but external) complex formation between CDs and their guests.…”
Section: Enantioselective Nmr Signal Splitting In Aqueous and Nonaquesupporting
confidence: 92%
See 4 more Smart Citations
“…The significant signal splittings were observed not only for the aromatic but also for some alkyl chain protons of propranolol (data not shown). Thus, in confirmation to our previous results [10,14], not only can enantioseparation in CE but also signal splitting in 1 H NMR spectra be observed without inclusion (but external) complex formation between CDs and their guests.…”
Section: Enantioselective Nmr Signal Splitting In Aqueous and Nonaquesupporting
confidence: 92%
“…2A). This was quite surprising, as according to our previous study [10] and to the results reported in Section 3.5, propranolol does not form an inclusion complex with HDAS-b-CD in the aqueous buffer used in this study. Hence, the aromatic (as well as other) protons of propranolol are not included into the cavity of HDAS-b-CD.…”
Section: Enantioselective Nmr Signal Splitting In Aqueous and Nonaquesupporting
confidence: 39%
See 3 more Smart Citations